2022
DOI: 10.1002/adma.202110455
|View full text |Cite
|
Sign up to set email alerts
|

A Magnetically Separable Pd Single‐Atom Catalyst for Efficient Selective Hydrogenation of Phenylacetylene

Abstract: an external magnetic field since it contains magnetic Ni particles. Thus, the combination of atomically dispersed metallic atoms and magnetic Ni@G support can pave the way to design more promising catalysts for selective hydrogenation reactions in industrial applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…Reaction rates at different temperatures were measured and the activation energies (E a ) of Pd/Nb 2 C were fitted to be 39.5 kJ/mol (Fig. 5c ), suggesting the superiority of Pd/Nb 2 C among Pd-based catalyst reported previously under similar reaction conditions 56 , 57 . To shed light on the original of excellent catalytic performance of Pd/Nb 2 C, the experiments of kinetic isotope effect (KIE) were accomplished using D 2 as feed gas in phenylacetylene hydrogenation 58 , 59 .…”
Section: Resultssupporting
confidence: 63%
“…Reaction rates at different temperatures were measured and the activation energies (E a ) of Pd/Nb 2 C were fitted to be 39.5 kJ/mol (Fig. 5c ), suggesting the superiority of Pd/Nb 2 C among Pd-based catalyst reported previously under similar reaction conditions 56 , 57 . To shed light on the original of excellent catalytic performance of Pd/Nb 2 C, the experiments of kinetic isotope effect (KIE) were accomplished using D 2 as feed gas in phenylacetylene hydrogenation 58 , 59 .…”
Section: Resultssupporting
confidence: 63%
“…Reaction rates at different temperatures were measured and the activation energies (E a ) of Pd/Nb 2 C were tted to be 39.5 kJ/mol (Fig. 5c), suggesting the superiority of Pd/Nb 2 C among Pd-based catalyst reported previously under similar reaction conditions 50,51 . To shed light on the original of excellent catalytic performance of Pd/Nb 2 C, the experiments of kinetic isotope effect (KIE) were accomplished using D 2 as feed gas in phenylacetylene hydrogenation 52,53 .…”
Section: Resultssupporting
confidence: 60%
“…Impressively, the TOF value increases after the CpCo- fragments bonding on Pt/SiO 2 and further increases with the CpCo- coverage. The highest TOF on 200CpCo-Pt/SiO 2 (17 964.0 h –1 ) is also higher than most reported Pt and Pd-based catalysts. In addition, the reusability of 200CpCo-Pt/SiO 2 was tested. It is found that the selectivity and conversion are nearly similar after the consecutive recycling runs (Figure S14c).…”
Section: Resultsmentioning
confidence: 92%